The Totem Handshake Policy During the Pandemic: Between Legal Compliance and Individual Moral Autonomy - Sarip, Sarip; Nasywa, Hamidah; Ayu Anggraeni, Putri (Cv. Kalimasada Group, 2025)
This research explores the state's emergency policy during the COVID-19 pandemic, particularly its moral dilemma in confronting the cultural tradition of handshakes and the symbolic implementation of the “Totem Handshake.” The state’s approach, limited to non-binding recommendations and symbolic language such as “physical distancing” and “social distancing,” raises critical questions about legal effectiveness. The study finds that symbolic appeals, though lacking coercive force, have a psychological and cultural impact resembling a form of “state magic” that influences public behavior. While such appeals were widely accepted, their legal standing remains weak, and the success of compliance is ambiguous—did people obey state messaging, or were they simply afraid of the virus? The research argues that the state faces greater social and legal risks if it enforces coercive regulations to restrict cultural practices. The public response varied, reflecting differing interpretations of state authority. Ultimately, this study highlights the state's reliance on symbolic language as a soft-law mechanism during moments of moral crisis. It suggests that in future emergencies, legal obedience may require not only formal authority but also cultural sensitivity and moral legitimacy, especially when asking citizens to temporarily abandon deeply rooted social traditions like handshakes.